Pembelajaran Matematika Sekarang dan yang akan Datang Berbasis Karakter - Hasratuddin Hasratuddin (Didaktik Matematika, 2014)
Education through learning with heart is an attempt to humanize humans. When human behaviour today does not show as a caliph who keep the peace in life, and life as a shortcut behaviour deemed inappropriate, then the system needs to be reformed education and teaching. A mathematical model of learning that form a logical thinking skills, critical, creative, consistent and growing confidence and character is a student-centered learning, among others through the stages constructive, interactive, and reflective.